Stability assessment of 132kV Sabah grid-connected solar pV system - Liau, Agnes Siau Wei (2014)
The population of the world is getting bigger and bigger, and the demand of electricity is thus increased from year to year. The fossil fuel which used to generate electricity are getting high demand and it will be exhausted one day. Apart from that, the rapid fluctuation and increase of fossil fuel price and the environment concerns related to the increase in the pollution and greenhouse gas emission accelerate the use of solar power to generate electricity. Therefore in this project, system study will be carried out to determine the largest possible capacity of Photovoltaic (PV) solar power generation to be injected to the Northern Grid of SESB’s 132kV network.The system study was first carried out by injection of 25MW of solar PV plant and the result showed some violation in the transformer at 275/132kV Segaliud substation. With that mitigation 1 and 2 were adopted in further system study to search for maximum solar capacity which the grid could sustain. Mitigation 1 is by adding one transformer to the overloaded existing transformer at 275/132kV Segaliud substation, whereas mitigation 2 is by limiting the power transfer from west coast grid to east coast grid. At the end of the study, the largest possible capacity of solar PV could be generated is 75MW with findings fulfilling the Planning Criteria. However this capacity are subjected to the land availability and also the solar irradiance factors in Northern of Sabah.